The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/ijerph18084285
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on the Cognition of People with Dementia

Abstract: (1) Background: To limit the COVID-19 outbreak, the Italian government implemented social restrictions that may have had psychological and cognitive repercussions on people with dementia. We aimed to analyze cognitive decline during the pandemic year in people evaluated in a memory clinic in northern Italy, the epicenter of COVID-19 spread. (2) Methods: A single-center retrospective study was carried out, including individuals with annual follow-up evaluated in three different years (2020-GROUP, 2019-GROUP, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…Furthermore, the impact of the COVID-19 pandemic and its associated social restrictions has been observed in the progression of cognitive impairment in people with dementia and in the exacerbation of neuropsychiatric symptoms in people with chronic neurological diseases [155]. One study examining the effects of quarantine in patients with Alzheimer's disease (AD), frontotemporal dementia (FTD), vascular dementia (VD) and dementia with Lewy bodies (DLB) found that approximately 60% of patients experienced changes in behavioural and psychological symptoms (BPSD) after one month of isolation, including worsening of previous symptoms (51.9%) or emergence of new symptoms (26%).…”
Section: The Covid-19 Pandemic As a Psychological Stress Factormentioning
confidence: 99%
“…Furthermore, the impact of the COVID-19 pandemic and its associated social restrictions has been observed in the progression of cognitive impairment in people with dementia and in the exacerbation of neuropsychiatric symptoms in people with chronic neurological diseases [155]. One study examining the effects of quarantine in patients with Alzheimer's disease (AD), frontotemporal dementia (FTD), vascular dementia (VD) and dementia with Lewy bodies (DLB) found that approximately 60% of patients experienced changes in behavioural and psychological symptoms (BPSD) after one month of isolation, including worsening of previous symptoms (51.9%) or emergence of new symptoms (26%).…”
Section: The Covid-19 Pandemic As a Psychological Stress Factormentioning
confidence: 99%
“…Therefore, all societies affected by the SARS-CoV-2 infection have gradually declared social distancing and home-confinement to prevent the spread of the new infection. According to Tondo et al [1], the COVID-19 pandemic generates substantial changes in routine activities, restrictions of movement and has a considerable impact on people's psychological and cognitive levels. Furthermore, it 2 of 26 creates challenges for the healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it 2 of 26 creates challenges for the healthcare system. The main problems in dementia during this pandemic period are related to an increase of sufferers of cognitive impairment [1].…”
Section: Introductionmentioning
confidence: 99%
“…Cumulative research results clearly indicate the beneficial effects of physical activity (PA) on brain health, and some reports have suggested that physical inactivity in older adults caused by COVID-19 pandemic-related lockdowns have had a negative impact on brain health ( Fiorenzato et al, 2021 ; Ismail et al, 2021 ; Tondo et al, 2021 ; Znazen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%